2007
DOI: 10.1002/qj.79
|View full text |Cite
|
Sign up to set email alerts
|

A variational data assimilation system for ground‐based GPS slant delays

Abstract: Tropospheric delay affects the propagation of the microwave signals broadcast by the Global Positioning System (GPS) satellites. Geodetic processing software enable estimation of this effect on the slanted signal paths connecting the satellites with the ground-based receivers. These estimates are called slant delay (SD) observations and they are potentially of benefit in numerical weather prediction.The three-dimensional variational data assimilation system of the High-Resolution Limited-Area Model (HIRLAM 3D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…They calculated this error using data from a German observation network and European mesoscale model predictions. Järvinen et al (2007) inferred a ZTD error of 11 mm from a comparison of modeled and observed STDs.…”
Section: B Observational Errormentioning
confidence: 99%
See 3 more Smart Citations
“…They calculated this error using data from a German observation network and European mesoscale model predictions. Järvinen et al (2007) inferred a ZTD error of 11 mm from a comparison of modeled and observed STDs.…”
Section: B Observational Errormentioning
confidence: 99%
“…Furthermore, the observational error depends on the elevation angle. Järvinen et al (2007) and Bauer et al (2011) used the same type of error model. By comparing GPS-STD assimilation with GPS-PWV assimilation and considering the GPS-ZTD error, we estimated that the GPS-STD error in the zenith direction was 50 mm and adopted the error model below (Eq.…”
Section: B Observational Errormentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, JÄRVINEN et al (2007) analyzed the data assimilation of hypothetical and real STD (Slant Total Delay) observations in the framework of the HIRLAM (High-Resolution Limited Area Modeling) 3DVAR (3-dimensional variational assimilation) system. The experiments with hypothetical data showed that their assimilation results in reasonable specific humidity analysis increments.…”
Section: Introductionmentioning
confidence: 99%